The Impact of Design Parameters on Energy Demand for Office Renovation - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Chapter 6 showed that the office layout and desk location were the most influential design factors for the thermal and visual comfort of users, and layout and orientation were most influential for psychological comfort in office buildings. Office design parameters were analysed to optimise user satisfaction in relation to indoor environmental and organisational quality in office buildings by showing predictable models. However, the predicted satisfaction models had not been tested in terms of energy performance. Therefore, this chapter evaluates the energy performance of the predicted models by computational assessment.a Section 7.2 explains the energy simulation scheme, model typologies, and simulation parameters. Section 7.3 presents the comparison of energy simulation results based on three design factors such as office layout, orientation and WWR. The results present the differences of the energy demand according to the alternative office typologies and contribution of design factors. The annual energy demand of 24 models are compared on the basis of different model typologies, and present the most energy-efficient typologies in section 7.4.